Proceedings of 1994 33rd IEEE Conference on Decision and Control
DOI: 10.1109/cdc.1994.410903
|View full text |Cite
|
Sign up to set email alerts
|

Design and control of a simplified Stewart platform for endoscopy

Abstract: This paper presents the development of a workspace controller for a newly designed platform. The platform is designed to manipulate endoscopic tools and is actuated by tendons to meet the small scale requirements i n endoscopy. The tendon actuation provides challenges to the controller design since the number of degrees of freedom equals the number of tendons. In typical tendon-driven systems, the number of tendons is greater than the number of degrees of freedom. This paper presents the kinematic and dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
0
12
0
2
Order By: Relevance
“…In general, these studies are kinematic analysis of the parallel mechanisms (forward / inverse kinematic analysis, [2][3][4][5][6]), dynamic behavior, [7], control, [8][9][10], design of different simulators, [11][12], and manufacturing, [4]. Among these, kinematic analysis, especially, research for mechanisms resulting simpler mathematical solutions to reduce computation time is very significant.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies are kinematic analysis of the parallel mechanisms (forward / inverse kinematic analysis, [2][3][4][5][6]), dynamic behavior, [7], control, [8][9][10], design of different simulators, [11][12], and manufacturing, [4]. Among these, kinematic analysis, especially, research for mechanisms resulting simpler mathematical solutions to reduce computation time is very significant.…”
Section: Introductionmentioning
confidence: 99%
“…He also noticed that the layout of the joint centers on the platforms is extremely important: the closer the base is to a triangle, and the platform to a regular hexagon, the less powerful the actuators will have to be. Wendlandt (616) investigates the influence of a spring component on the dynamics equations of a micro-robot. We must also mention the approach of dynamic balancing by Xi (628): the tool holder is used as a counterweight to reduce the changes in the inertia matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Wendlandt et al [30] demonstrated a platform driven by three tendons actuated by dc motors capable of 90 deflections and a 50-ms step response.…”
Section: B Gastrointestinal Endoscopymentioning
confidence: 99%